Pengenalan Komputer Disertai Pelatihan Mengetik bagi Anak Remaja Pusat Pengembangan Anak 434 Gloria Genyem Kelurahan Tabri Provinsi Papua - Yapinus, Pin Panji; Wong, Hendry; Lehman, Andrew Sebastian; Tanubrata, Markus; Chandra, Jonathan; Loekito, Jimmy Agustian; Tjiharjadi, Semuil; Wijaya, Marvin Chandra; Bayu P., Emmanuel F. Sigit Bayu P; Parera, Rudianov Z.A.; Wibawa, Oswald Vierly Yudha; Rusli, Christian; Cahyadi, Tonny; Armandi, Daniel Zifa; Sinukaban, Christopher Junius (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
Knowledge in the computer field is needed by everyone nowadays. In Papua Province, there is a Child Development Center (PPA 434) which aims to train and teach children in various fields of knowledge. Despite limited computer and internet facilities, training was provided to children to improve their computer skills. The material provided in this training is knowledge in the field of computer hardware, software and the ability to type using a computer. The training is provided using a distance learning system regularly every week for four meetings. The training results were measured using pre-test and post-test, which showed an increase in literacy skills in the computer field after participating in this training.